(untitled) (Eurasian Scientific Herald, 2022)
The life and scientific activity of one of the famous Hanafi scholars of Movarounnahr, the scholar Abu Lais Samarkandi, has been widely studied by many researchers of our motherland and foreign countries. In these studies, the scholar is presented as a famous Islamic jurist and mufassir (translator and commentator of the Holy Qur’an and its meanings). This article pays special attention to the study of the aspects of Abu Lais Samarkandi’s scientific heritage in kalam (Qur’an) knowledge. His contribution to the development of Moturidism as one of the hanafi-moturidi scholars was revealed